THE IMPACT OF TEACHING-SCHOOL STUDENTS WITH A PESANTREN EDUCATION BACKGROUND AS FUNDS OF IDENTITY: A SOCIOLOGICAL ANALYSIS - Tomy Kartika Putra; Rohmad Arkam (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2022)
Teaching-school students with a pesantren education background have a source of identity with rich Islamic values. Research-based on their identity formation is essential. They need to consider their experiences to help them when entering college. This study aims to determine the components of the identity sources of new students in the Department of English education at one of universities in East Java. By referring to the fund's identity framework, this study analyzes self-portraits of teaching-school students to find the origins of student identity formation. This research employs observation techniques and in-depth interviews with four teaching school students with pesantren educational backgrounds. The study results indicate that teaching-school students with pesantren backgrounds have sources of identity formation with social, valuative, practical, institutional, and disciplinary categories. From a sociological perspective, identity formation's origins are part of positive social capital with pedagogical and methodological implications in the teaching process.Mahasiswa keguruan yang mempunyai latar belakang pendidikan pesantren membawa sumber identitas yang kaya nilai Islam. Penelitian mengenai sumber pembentuk identitas yang mereka miliki penting dilakukan. Pengalaman yang mereka bawa perlu dirangkul sebagai upaya untuk membantu mereka ketika masuk dalam perguruan tinggi. Penelitian ini bertujuan untuk mengetahui komponen-komponen sumber identitas mahasiswa baru Pendidikan Bahasa Inggris. Dengan mengacu pada kerangka funds of identity, penelitian ini menganalisis self-portrait mahasiswa-keguruan untuk mengetahui sumber pembentuk identitas mahasiswa. Data dikumpulkan melalui teknik observasi dan wawancara mendalam terhadap 4 orang mahasiswa-keguruan dengan latar belakang pendidikan pesantren. Hasil penelitian menunjukkan bahwa mahasiswa keguruan berlatar belakang pendidikan pesantren mempunyai sumber pembentuk identitas, yakni social, valuative, practical, institutional, and disciplinary. Secara Sosiologis, sumber pembentuk identitas tersebut merupakan bagian dari modal sosial yang positif dan memiliki implikasi pedagogi dan metodologi dalam proses pengajaran.